Penerapan Strategi Inovatif Dalam Pembelajaran Pendidikan Agama Islam (PAI) Untuk Meningkatkan Pemahaman Peserta Didik - Intan Tsamratul Ain H; Ismi Nofitra; Fazrul Azmi; Riddwal Trisoni; Muhammad Yahya (TEKNO AULAMA: Jurnal Teknologi Pendidikan Islam, 2025)
Innovative strategies are intended to apply innovative learning methods that differ from conventional methods to achieve educational goals more efficiently and effectively. This study aims to analyze and evaluate the application of innovative strategies in Islamic religious education (PAI) learning as an effort to improve students' understanding of religious material. The research method used in this study is a literature review by analyzing various journal articles, books, and scientific publications relevant to the topic of innovative Islamic religious education (PAI) learning over the past 10 years. The results show that the use of innovative approaches in PAI learning results in a significant increase in student understanding. Innovative learning can accommodate various learning styles, create an interesting and meaningful learning atmosphere, and improve critical thinking skills. Methods such as technology-based learning, active approaches, contextual approaches, and the use of creative media have proven effective in increasing student motivation and helping them understand and apply Islamic values ​​in everyday life. However, several challenges remain in implementing innovative strategies. The conclusion of this study confirms that innovation in PAI learning is crucial to address the challenges of 21st-century education. Islamic Religious Education teachers must innovatively combine technology, active methods, and contextual approaches to provide learning that not only provides knowledge but also builds character and understanding of Islamic teachings in a way that can be applied in real life.